Analysis of Lampung Province Website Standardization - Muhammad Naufal; Siti Sarohmawati (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The Lampung Provincial Government has an e-government website information system with the site address https://lampungprov.go.id/ which plays an important role in managing information to the public, especially to the people of Lampung. On October 31, 2022, the website of the Lampung Provincial Government was visited by 556 thousand visitors, which was measured using an analytical tool, namely Semursh Rank. The Lampung Province website got a score of 77.8, and the website has met the standards that refer to the Law of the Republic of Indonesia. This study uses a quantitative descriptive method to measure the information contained on the Lampung Provincial Government website by measuring the rating scale table and its correlation level.Keywords—government, lampung, website, analysis, content